The labeling of unsaturated γ-hydroxybutyric acid by heavy isotopes of hydrogen: iridium complex-mediated H/D exchange by C─H bond activation vs reduction by boro-deuterides/tritides - Marek, Aleš; Pedersen, Martin H F; Vogensen, Stine B; Clausen, Rasmus P; Frølund, Bente; Elbert, Tomáš (Journal of labelled compounds & radiopharmaceuticals, 2016)
3-Hydroxycyclopent-1-ene-1-carboxylic acid (HOCPCA (1)) is a potent ligand for high-affinity γ-hydroxybutyric acid binding sites in the central nervous system. Various approaches to the introduction of a hydrogen label onto the HOCPCA skeleton are reported. The outcomes of the feasible C─H activation of olefin carbon (C-2) by iridium catalyst are compared with the reduction of the carbonyl group (C-3) by freshly prepared borodeuterides. The most efficient iridium catalysts proved to be Kerr bulky phosphine N-heterocyclic species providing outstanding deuterium enrichment (up to 91%) in a short period of time. The highest deuterium enrichment (>99%) was achieved through the reduction of ketone precursor 2 by lithium trimethoxyborodeuteride. Hence, analogical conditions were used for the tritiation experiment. [3 H]-HOCPCA selectively labeled on the position C-3 was synthetized with radiochemical purity >99%, an isolated yield of 637 mCi and specific activity = 28.9 Ci/mmol.
Keywords: Alkenes; Deuterium; Ligands; Catalysis; ligandy; tritium-labeled γ-hydroxybutyric acid; borotritides; tritium; oxidace-redukce; iridium catalyst; Deuterium Exchange Measurement; deuterium; iridium; hydrogen/deuterium exchange; Isotope Labeling; izotopové značení; Hydroxybutyrates; alkeny; Tritium; Boron; Iridium; vodík-deuteriová výměna; C─H activation; Oxidation-Reduction; hydroxybutyráty; katalýza; bor